Statistical Analysis of Annual and Semi-Annual Sum of Atmospheric Precipitation Data for 59 Municipalities (11 Regions) of Georgia with Landslide Hazard Zones from 2015 to 2024 - Amiranashvili, Avtandil G.; Brocca, Luca; Chelidze, Tamaz L.; Svanadze, David T.; Tsamalashvili, Tamar N.; Varamashvili, Nodar D. (Journals of Georgian Geophysical Society, 2025)
The article presents the results of statistical analysis of data from 62 meteorological stations of Georgia located in the territories of 59 municipalities (11 regions) of Georgia with dangerous landslide zones on semi-annual and annual sum of atmospheric precipitation. The observation period is from 2015 to 2024. In particular, empirical (map) and calculated model of distribution of annual sum of atmospheric precipitation averaged over the territories of municipalities were obtained; the relationships of semi-annual and annual sum of atmospheric precipitation averaged over the territories of municipalities and regions with the altitude and longitude of the area, etc. were studied. In the future, it is planned to use the results of this work for a more detailed study of the relationship between precipitation and the activation of landslide processes on a climatic time scale.